Implementation of Relationship Marketing Sharia Perspective In Sharia Microfinance Institutions In Madura - Fathor AS; Fatimatul Fatmariyah; Sirajul Arifin; Muh. Syarif (Journal Research of Social Science, Economics, and Management, 2023)
The market share of Islamic banking is still very small, so there needs to be a proper marketing strategy to overcome it, one of which is Sharia relationship marketing. The purpose of this research is to analyze the implementation of sharia relationship marketing at BPRS Bhakti Sumekar Sumenep. The research method used is a descriptive method of quantitative approach. The results showed that BPRS Bhakti Sumekar Sumenep has assimilated sharia relationship marketing quite well, it is shown from the results of respondents' assessment of the dimensions used in the study.